The association of asthma, atopic dermatitis, and allergic rhinitis with peripartum mental disorders. Issue 10 (3rd December 2021) - Ren, Tai; Chen, Jiawen; Yu, Yongfu; He, Hua; Zhang, Jun; Li, Fei; Svendsen, Katrine; Obel, Carsten; Wang, Hui; Li, Jiong
Abstract: Background: Atopic diseases are characterized by dysregulated inflammatory response, which may incur the onset of peripartum mental disorders, but the impact remains unknown. This study examined whether and to what extent the history of atopic diseases is associated with newly onset peripartum mental disorders. Methods: Using population‐based registries, we identified all primiparous women who gave birth to live singletons in Denmark during 1978–2016 ( n = 937, 422). The exposure was hospital contact due to the three major types of atopic diseases—asthma, atopic dermatitis, and allergic rhinitis—before conception. The primary outcome was any hospital contact for mental disorder during pregnancy and 1‐year postpartum, which was further classified into affective disorders, neurotic, stress‐related and somatoform disorders, and substance abuse. The follow‐up started from the date of conception and ended at the date of the first diagnosis of mental disorders, 1‐year postpartum, death, emigration, or December 31, 2016, whichever came first. Cox regression was used, adjusted for calendar year, age at childbirth, education, residence, and Charlson comorbidity index. Results: A total of 24, 016 (2.6%) women received diagnosis of at least one of the three atopic diseases before conception (asthma, 1.7%; atopic dermatitis, 0.6%; and allergic rhinitis, 0.8%). Exposure to asthma, atopic dermatitis, or allergic rhinitis was associated with a 37% increased overall risk of peripartum mental disorders (hazard ratio [HR], 1.37; 95% confidence interval [CI], 1.27–1.49). Higher risks were observed among women with more frequent hospital contacts for atopic disease (HR, 1.80; 95% CI, 1.37–2.35; ≥5 times), and with recent hospital contacts for atopic disease (HR, 1.74; 95% CI, 1.48–2.06; within 2 years before conception). Specific associations were observed between asthma and neurotic, stress‐related and somatoform disorders (HR, 1.40; 95% CI, 1.21–1.62), and between atopic dermatitis and substance abuse (HR, 1.62; 95% CI, 1.12–2.34). Conclusions: History of asthma, atopic dermatitis, and allergic rhinitis before conception was associated with increased risks of peripartum mental disorders. Women who have atopic diseases before pregnancy may benefit from systematic mental health monitoring.